1998
DOI: 10.4269/ajtmh.1998.58.183
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, blinded, comparative trial of one pepsin-digested and two whole IgG antivenoms for Bothrops snake bites in Uraba, Colombia. The Regional Group on Antivenom Therapy Research (REGATHER).

Abstract: The therapeutic efficacy and the incidence of early antivenom reactions (EARs) were compared in a clinical trial performed in 79 patients bitten by Bothrops sp. in Urabá, Colombia. Patients were randomized into three groups according to the antivenom administered: A (n ϭ 30, Butantan polyspecific, pepsin-digested Bothrops antivenom); B (n ϭ 27, Butantan polyspecific, whole IgG Bothrops antivenom); and C (n ϭ 22, Colombian commercial, monovalent, whole IgG Bothrops antivenom). The groups were comparable in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
1
17

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 22 publications
2
62
1
17
Order By: Relevance
“…Segura et al (6) observed that the reduction of phenol to a concentration of 0.15 g% maintains the physical stability of antivenoms and decreases their liability of forming aggregates (6). Other researchers corroborate such finding, especially if the protein content is elevated, which may lead to loss of antivenom activity and to adverse reactions due to activation of the immune response (4,21,(26)(27)(28)(29)(30). At the same time, the decrease of m-cresol concentrations may diminish antivenom toxicity to humans, particularly in certain circumstances in which high doses are required, such as in the two cases mentioned by Buntain (31) and Ganthavorn (32) (750 to 1150 mL of antivenom).…”
Section: Discussionsupporting
confidence: 59%
“…Segura et al (6) observed that the reduction of phenol to a concentration of 0.15 g% maintains the physical stability of antivenoms and decreases their liability of forming aggregates (6). Other researchers corroborate such finding, especially if the protein content is elevated, which may lead to loss of antivenom activity and to adverse reactions due to activation of the immune response (4,21,(26)(27)(28)(29)(30). At the same time, the decrease of m-cresol concentrations may diminish antivenom toxicity to humans, particularly in certain circumstances in which high doses are required, such as in the two cases mentioned by Buntain (31) and Ganthavorn (32) (750 to 1150 mL of antivenom).…”
Section: Discussionsupporting
confidence: 59%
“…7,8 However, various studies have shown that both types of antivenoms can activate the complement system in vitro 9,10 and induce EARs in patients. 11,12 Some data highlight the impact of the fractionation protocol on the induction of EARs. It was shown that IgG antivenom precipitated by ammonium sulphate had more aggregates and induced a higher incidence of EARs than IgG antivenom precipitated by caprylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…In several experimental and clinical trials it has been demonstrated that antivenoms are of limited value to stop edema progression within the first 12-24 h of treatment, while they are highly efficient in restoring blood coagulation status within the same time interval (7,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The antivenoms commonly used for the serotherapy of snakebites show a very limited efficacy in the neutralization of edema, not only due to the variety of components inducing this alteration, but also due to its rapid onset (6)(7)(8). Defibrinating (in vivo) and coagulant (in vitro) effects are produced by thrombin-like toxins present in the venom which induce fibrinogen consumption and incoagulable blood that may favor systemic bleeding (9).…”
Section: Introductionmentioning
confidence: 99%